Dynamics of Family Law in the Context of Globalization: Comparison Between Legal Systems - Fatima Sajan (ILAW, 2024)
This article explores the dynamics of family law within the context of globalization through a comparative study of different legal systems. This article aims to analyze and compare the dynamics of family law across different legal systems within the context of globalization. It examines how globalization influences family law, highlighting both the convergence and divergence of legal practices across various jurisdictions, including civil law, common law, and religious law traditions. The resulting study analyzes the impact of international treaties and conventions on domestic family law, revealing significant areas of uniformity and persistent variations driven by cultural and religious norms. Practical challenges in implementing these international standards are also discussed, alongside the role of supranational entities in shaping family law. This article offers insights into the evolving landscape of family law in a globalized world by providing a comprehensive analysis that includes case studies and empirical data. It suggests avenues for future research to enhance legal harmonization and address cross-border family law issues.